2009
DOI: 10.1177/1753465809102662
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and depression: is smoking cessation effective?

Abstract: Patients with depression tend to have a higher rate of smoking and an increased severity of nicotine dependence. It seems that common genetic and environmental factors may influence the bimodal relationship between smoking and depression. Nicotine has some positive reinforcing/rewarding effects that may affect people with mood disorders and smoking is also used as a 'relief medication' in order to ameliorate symptoms of depression, as it is already known that nicotine, which is the major psychoactive ingredien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…In conclusion, despite the fact that some of these studies failed to identify a reciprocal relationship between tobacco addiction and depression ( 30 , 37 , 108 ), the relationship seems to be bidirectional ( 113 ). As described earlier, tobacco dependence predicts the development of depressive symptoms and MD, while a history of MD predicts the onset of daily smoking and progression to tobacco dependence.…”
Section: Tobacco Smoking Personality Traits and Psychiatric Conditimentioning
confidence: 92%
“…In conclusion, despite the fact that some of these studies failed to identify a reciprocal relationship between tobacco addiction and depression ( 30 , 37 , 108 ), the relationship seems to be bidirectional ( 113 ). As described earlier, tobacco dependence predicts the development of depressive symptoms and MD, while a history of MD predicts the onset of daily smoking and progression to tobacco dependence.…”
Section: Tobacco Smoking Personality Traits and Psychiatric Conditimentioning
confidence: 92%
“…This decrease produced during treatment in all the groups might be due to the fact that the treatment includes psychological strategies that may also be useful for mood management (e.g., problem solving, stress management), but after completing the treatment or if there is a relapse, these positive effects on mood disappear. Ischaki and Gratziou (2009) and Brodbeck et al (2014) point to self-efficacy and self-esteem as mediating variables between depression and smoking cessation. Compared with relapsers or with those who never stopped smoking, those who remain abstinentdespite not differing in depression scores at the beginning of treatment-probably use the strategies to maintain abstinence that they learned throughout the treatment, thereby increasing their self-efficacy and the likelihood of not relapsing (Marlatt and Donovan, 2005).…”
Section: Smokers (N¼ 49)mentioning
confidence: 99%
“…Similar to the link between anxiety disorders and smoking, depression and nicotine dependence have also a reciprocal relationship (Ischaki & Gratziou, 2009; John, Meyer, Rumpf, & Hapke, 2004). Previous studies have shown that depression symptoms are important determinants of smoking initiation, maintenance, and cessation, whereas nicotine dependence is associated with vulnerability for depression (Breslau, Kilbey, & Andreski, 1991; Fergusson, Goodwin, & Horwood, 2003; Glassman et al, 1990; Hall, Muñoz, Reus, & Sees, 1993; Morrell & Cohen, 2006; Paperwalla, Levin, Weiner, & Saravay, 2004).…”
Section: Effects Of Nicotine Dependence Withdrawal and Nachr Regmentioning
confidence: 99%